2004
DOI: 10.1007/s10875-004-6241-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mucosal Lymphocyte Cytokine Profiles in Children with Autism and Gastrointestinal Symptoms: Mucosal Immune Activation and Reduced Counter Regulatory Interleukin-10

Abstract: A lymphocytic enterocolitis has been reported in a cohort of children with autistic spectrum disorder (ASD) and gastrointestinal (GI) symptoms. This study tested the hypothesis that dysregulated intestinal mucosal immunity with enhanced pro-inflammatory cytokine production is present in these ASD children. Comparison was made with developmentally normal children with, and without, mucosal inflammation. Duodenal and colonic biopsies were obtained from 21 ASD children, and 65 developmentally normal paediatric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 20 publications
7
126
0
3
Order By: Relevance
“…89 In addition to abnormalities in the adaptive immune system in children with ASD, a number of differences have been noted in the innate immune system. Most relevant of these is the increase in proinflammatory cytokines, and the downregulation of IL-10, 51,55,90 findings that correspond to the function of monocytes where mTOR is inhibited. 91 …”
Section: Deficits In Immune and Neurological Signaling Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…89 In addition to abnormalities in the adaptive immune system in children with ASD, a number of differences have been noted in the innate immune system. Most relevant of these is the increase in proinflammatory cytokines, and the downregulation of IL-10, 51,55,90 findings that correspond to the function of monocytes where mTOR is inhibited. 91 …”
Section: Deficits In Immune and Neurological Signaling Pathwaysmentioning
confidence: 99%
“…50 Studies that assess cytokine levels in the periphery have often shown similar increases in proinflammatory cytokines, [51][52][53][54][55] as well as decreases in anti-inflammatory cytokines such as IL-10 24,52 and TGF␤. 56 However, not all studies have shown a consistent pattern of specific cytokines, and data so far collected suggest a complex pattern of immune activation that varies among different subgroups of individuals with ASD.…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…[31][32][33][34] Duodenal lymphocytosis in autistic children, whether or not associated with the lactase deficiency frequently recorded in these patients, also has been observed. 35 …”
Section: Hypersensitivity To Other Alimentary Proteinsmentioning
confidence: 99%